Correlation Analysis of Community Governance and Mental Health Based on Big Data and Intelligent Computing - Ma, Zhenyue (Frontiers in Psychology, 2022)
With the continuous development of the era of big data, community management plays an important role in people's mental health. Improve people's mental health through the use of big data to improve governance of the community. To solve the problem, sequence segmentation is used in feature extraction, histogram absolute difference calculation and K-means intelligent algorithm, to analyze the existing problems one by one. Research shows that it is possible to systematically govern the community through big data and intelligent computing, so that community residents can live a higher quality of life. In order to get rid of psychological problems, it can be solved by establishing special psychological support institutions in the community and strengthening the role of the government in community management.